2018
DOI: 10.1080/10669817.2018.1475693
|View full text |Cite
|
Sign up to set email alerts
|

Instrument-assisted soft tissue mobilization and proprioceptive neuromuscular facilitation techniques improve hamstring flexibility better than static stretching alone: a randomized clinical trial

Abstract: Objectives: Tight hamstrings contribute to inefficiency of movement and increased risk for injury. Static stretching is the most common intervention for this problem, but the use of alternatives like instrument-assisted soft tissue mobilization (IASTM) and proprioceptive neuromuscular facilitation (PNF) is increasing among clinicians. This study examined two prospective studies with the common aim of demonstrating the effectiveness of IASTM or PNF over static stretching for improving hamstring tightness. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
1
32
1
8
Order By: Relevance
“…14,15 Although both PNF hamstring stretching and static hamstring stretching can effectively improve hamstring flexibility, it is unclear whether one of these exercises is superior. 5,[16][17][18] While some previous studies showed no significant differences in hamstring flexibility between the two hamstring stretching exercises, 16,17 others demonstrated that PNF hamstring stretching was superior to static hamstring stretching in terms of improved hamstring flexibility. 5,18 Although these previous studies compared the effects of static hamstring stretching to PNF hamstring stretching, 5,[16][17][18] they did not consider the newly-developed jack-knife stretching method.…”
Section: Journal Of Musculoskeletal Science and Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Although both PNF hamstring stretching and static hamstring stretching can effectively improve hamstring flexibility, it is unclear whether one of these exercises is superior. 5,[16][17][18] While some previous studies showed no significant differences in hamstring flexibility between the two hamstring stretching exercises, 16,17 others demonstrated that PNF hamstring stretching was superior to static hamstring stretching in terms of improved hamstring flexibility. 5,18 Although these previous studies compared the effects of static hamstring stretching to PNF hamstring stretching, 5,[16][17][18] they did not consider the newly-developed jack-knife stretching method.…”
Section: Journal Of Musculoskeletal Science and Technologymentioning
confidence: 99%
“…5,[16][17][18] While some previous studies showed no significant differences in hamstring flexibility between the two hamstring stretching exercises, 16,17 others demonstrated that PNF hamstring stretching was superior to static hamstring stretching in terms of improved hamstring flexibility. 5,18 Although these previous studies compared the effects of static hamstring stretching to PNF hamstring stretching, 5,[16][17][18] they did not consider the newly-developed jack-knife stretching method. Comparing the PNF hamstring and jack-knife stretching methods could help clinicians determine the best strategy for improving hamstring flexibility and decreasing mechanical stress due to excessive lumbar flexion caused by hamstring tightness.…”
Section: Journal Of Musculoskeletal Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…34 Researchers have found that FR may improve joint ROM at the shoulder, 35,36 lumbopelvis, 37,38 hip joint, [39][40][41][42][43][44][45] knee joint, 9,[45][46][47] and ankle. 48,49 IASTM has also been shown to improve joint ROM at the shoulder, 27,28,50,51,52 hip and knee joint, 51,53,54,55 ankle, 56 and spine. 57 The FB research has documented improved post intervention ankle joint ROM in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Birinci et al [11] reported significant improvements in elbow pain, range of motion (ROM), and arm function upon the application of PNF stretching in patients with elbow stiffness. Gunn et al [12] reported that PNF stretching is more effective for hamstring flexibility than static stretching. Malai et al [13] reported that PNF stretching immediately reduced low back pain, decreased lumbar lordosis angle, and increased transversus abdominis activation.…”
Section: Introductionmentioning
confidence: 99%